Substrate Specificity of SARS-CoV-2 Nsp10-Nsp16 Methyltransferase - Benoni, Roberto; Krafcikova, Petra; Baranowski, Marek R; Kowalska, Joanna; Boura, Evzen; Cahová, Hana (Viruses, 2021)
The ongoing COVID-19 pandemic exemplifies the general need to better understand viral infections. The positive single-strand RNA genome of its causative agent, the SARS coronavirus 2 (SARS-CoV-2), encodes all viral enzymes. In this work, we focused on one particular methyltransferase (MTase), nsp16, which, in complex with nsp10, is capable of methylating the first nucleotide of a capped RNA strand at the 2'-O position. This process is part of a viral capping system and is crucial for viral evasion of the innate immune reaction. In light of recently discovered non-canonical RNA caps, we tested various dinucleoside polyphosphate-capped RNAs as substrates for nsp10-nsp16 MTase. We developed an LC-MS-based method and discovered four types of capped RNA (m7Gp3A(G)- and Gp3A(G)-RNA) that are substrates of the nsp10-nsp16 MTase. Our technique is an alternative to the classical isotope labelling approach for the measurement of 2'-O-MTase activity. Further, we determined the IC50 value of sinefungin to illustrate the use of our approach for inhibitor screening. In the future, this approach may be an alternative technique to the radioactive labelling method for screening inhibitors of any type of 2'-O-MTase.
Keywords: virové regulační a přídatné proteiny; virus; hmotnostní spektrometrie; substrátová specifita; SARS-CoV-2; Gene Expression Regulation, Viral; metylace; virové nestrukturální proteiny; methyltransferasy; COVID-19; Mass Spectrometry; RNA, Viral; Methyltransferases; regulace exprese virových genů; RNA čepičky; Humans; RNA Caps; chromatografie kapalinová; methylation; Substrate Specificity; Viral Nonstructural Proteins; Viral Regulatory and Accessory Proteins; Chromatography, Liquid; Methylation; RNA virová; lidé; inhibitor